2006
DOI: 10.1128/aem.72.5.3245-3251.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Shiga Toxin Gene ( stx )-Positive and Intimin Gene ( eae )-Positive Escherichia coli Isolates from Wastewater of Slaughterhouses in France

Abstract: Wastewater samples from 12 slaughterhouses located in different regions in France were tested for the presence of stx-positive and eae-positive Escherichia coli isolates, and characteristics of the isolates obtained were determined. A total of 224 wastewater samples were collected in wastewater treatment plants at different stages of wastewater processing. Altogether, 5,001 E. coli isolates were obtained by colony counting and screened for the presence of stx and eae genes by multiplex PCR. stx-positive and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
(56 reference statements)
1
26
2
1
Order By: Relevance
“…In contrast, the E. coli strains were absent after treatment of effluent at the WWTP. These results are opposed to those obtained in several studies conducted in France and elsewhere (Vernozy-Rozand et al, 2002;Loukiadis et al, 2006). This difference could be justified by the various methods of wastewater treatment used in a wastewater treatment plant and the final destination of the treated water.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast, the E. coli strains were absent after treatment of effluent at the WWTP. These results are opposed to those obtained in several studies conducted in France and elsewhere (Vernozy-Rozand et al, 2002;Loukiadis et al, 2006). This difference could be justified by the various methods of wastewater treatment used in a wastewater treatment plant and the final destination of the treated water.…”
Section: Discussioncontrasting
confidence: 56%
“…Other studies showed the presence of eae-positive E. coli isolates in effluents from human and animal origin (Holler et al, 1999;Vernozy-Rozand et al, 2004;Garcia-Aljaro, 2005;Awais et al, 2007;Ayaz et al, 2014). Loukiadis et al (2006) detected 54 eaepositive E. coli isolates among 5,001 isolates from various effluents from 12 slaughterhouses in France. Here, it was confirmed that the prevalence of eae-positive E. coli isolates in effluents was very low.…”
Section: Discussionmentioning
confidence: 99%
“…Stx2e-producing strains also frequently occur in pigs (16), in the environment of pig farms (46), and as contaminants of wastewater from abattoirs (26). The low incidence of Stx2e strains in human patients could indicate that most of these strains cannot colonize or may infect but do not cause disease in humans.…”
mentioning
confidence: 99%
“…As populations of E. coli from environmental and animal origins may be important natural reservoirs of phages (at least of Stx-encoding phages) that infect E. coli (14,18,23,24), we next investigated the distribution of cif-encoding prophages in a large collection of E. coli isolates from human, animal, and environmental origins. The Cif-encoding prophages were found ubiquitously in E. coli isolates from different origins, countries, and time periods and were always found associated with the LEE.…”
mentioning
confidence: 99%